Integrating Organizational System and Contingency Theory in Educational Management: A Systematic Literature Review - Nurani; Junaina; Agus Pahrudin; Subandi; Encep Syafrudin (UIN Sunan Gunung Djati Bandung, 2026)
Educational management is increasingly complex due to policy changes, technological advancements, and dynamic social demands. These conditions require management approaches that are both systemic and context-sensitive. This study aims to systematically examine the application of organisational system theory and contingency theory in educational management and to identify patterns of their integration. A Systematic Literature Review (SLR) was conducted following the PRISMA 2020 guidelines. A total of 33 peer-reviewed journal articles published between 2015 and 2024 were retrieved from Scopus, Google Scholar, and DOAJ databases. Data were analysed using a thematic synthesis approach based on theoretical focus and implementation context. The findings indicate that organisational system theory emphasises integration, interdependence among subsystems, and organisational sustainability, while contingency theory highlights leadership flexibility and alignment between management strategies and environmental conditions. The integration of these two theories provides a more comprehensive and adaptive framework for improving educational management effectiveness, particularly within Islamic educational institutions. This study contributes to the development of context-sensitive and sustainable educational management theory.